Achievements and Challenges of Human Rights Protection Policy in Realizing Good Governance in Indonesia and China - M. Misbahul Mujib; Mustari Kurniawati Muchlas (Journal of Human Rights, Culture and Legal System, 2023)
The protection of human rights in public service institutions faces challenges in its effectiveness to achieve maximum protection. This is because there are many units and ranks of the bureaucracy that need to be given oversight and protection. A regional head cannot be given the entire burden of supervising the protection of human rights. This study aims to explore the policies of the Ombudsman Institute in Yogyakarta, Indonesia regarding the Protection of Human Rights, their relation to the achievements and challenges so as to realize good governance. The research is compared with the policies to protect human rights in Beijing, China. This quantitative research analyzes the legal gap from the problem of protecting human rights in work units with the principles of good general governance and the supervisory model in the institution. Finally, this research finds the effectiveness and success of the role of the Ombudsman Institute in Indonesia in protecting human rights in maintaining good governance. To address the problem of protecting human rights, the pattern of oversight by the Indonesian Ombudsman Institute uses an ideal pattern, namely extra-parliamentary synergy, parliamentary oversight, a social audit system and the use of technological facilities so that good governance is realized. Meanwhile, China still gets notes from the international world for human rights violations. Even so, reform of the Ombudsman bureaucracy in China is expected to resolve existing human rights protection issues.